PeopleSoft PeopleTools data management and upgrade handbook - Dean, Paula (McGraw-Hill, 2013)
Master Oracle's PeopleSoft PeopleTools Data Administration and Upgrade Toolset Maximize data integrity, maintain peak application performance, and keep your PeopleSoft environment up to date. PeopleSoft PeopleTools Data Management and Upgrade Handbook explains the latest techniques and provides best practices, case studies, and programming examples. Find out how to develop and deploy data mover scripts, audit database health, apply patches, and generate project comparison reports. This Oracle Press guide offers thorough coverage of Oracle's PeopleSoft life cycle management tools. Understand PeopleSoft PeopleTools architecture Manage metadata using PeopleSoft Application Designer Create and execute PeopleSoft Data Mover scripts Learn how to use PeopleSoft Data Archive Manager Read best practices for applying updates, patches, and fixes Implement PeopleSoft change control features Build automated functional tests Plan and execute application and platform upgrades.
Includes bibliographical references and index. - Print version record
Keywords: PeopleSoft software; Database management; Computer software -- Development; Business enterprises -- Computer networks; Logiciels PeopleSoft; Bases de données; Gestion; Entreprises; Réseaux d'ordinateurs; Business enterprises; Computer networks; Computer software; Development